R Contribution of Cocoa Farming to Farming Income in Tinete Village, Aere District, East Kolaka Regency - Randi Ashari; Nurcayah Nurcayah; Syamsinar Syamsinar (Fakultas Pertanian Universitas Muhammadiyah kendari, 2023)
Cocoa is a plantation crop that has export potential and is a livelihood for farmers in Tinete Village, Aere District. This study aims to determine the contribution of cocoa farming to farmers' income in Tinete Village, Aere District, East Kolaka Regency. The population in this study amounted to 106 cocoa farmers. by using the Slovin method obtained 32 samples. Data analysis in this study uses a quantitative-descriptive approach. To determine the income of cocoa farming using the income formula (Pd = TR-TC), with the Contribution formula: K = Pd/Prt x 100% The results of the study obtained that the average income from cocoa farming was Rp. 42,884,303, and the total average farmer's income is Rp. 8,251,917. The contribution of cocoa farming to the total income of farmers in Tinete Village, Aere District, East Kolaka Regency, based on the results of the author's calculations, obtained a contribution of 83.86%. Cocoa farming contributes very high because the contribution is above 50%. The amount of farmers' income depends on the area of ​​land and the availability of production infrastructure